2021
DOI: 10.3390/ijms22169035
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Proteins Bind to Hemoglobin and Its Metabolites

Abstract: (1) Background: coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been linked to hematological dysfunctions, but there are little experimental data that explain this. Spike (S) and Nucleoprotein (N) proteins have been putatively associated with these dysfunctions. In this work, we analyzed the recruitment of hemoglobin (Hb) and other metabolites (hemin and protoporphyrin IX-PpIX) by SARS-Cov2 proteins using different approaches. (2) Methods: shotgu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 71 publications
6
46
2
Order By: Relevance
“…In consistent with our analysis, a recent interatomics study shows that SARS-CoV-2 proteins interacts with ubiquitin ligases, kinases, lipid modifications, as well as proteins contain zinc finger, SH2, SH3, and PDZ domains [28], Supplementary Table S10. Additionally, PDZ-binding motifs (PBM) is crucial during SARS-CoV infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In consistent with our analysis, a recent interatomics study shows that SARS-CoV-2 proteins interacts with ubiquitin ligases, kinases, lipid modifications, as well as proteins contain zinc finger, SH2, SH3, and PDZ domains [28], Supplementary Table S10. Additionally, PDZ-binding motifs (PBM) is crucial during SARS-CoV infection.…”
Section: Discussionsupporting
confidence: 91%
“…(E) The sequence logo and consensus sequences of nsp1 C-terminus of coronaviruses. The figures(A-C) adopted from[28][29][30][31][32]; (D-E) from EBI portal (https://www.ebi.ac.uk/thornton-srv/ databases/cgi-bin/VarSite/GetPage.pl?home=TRUE, last accessed on 30 August 2021, UniProt ID: P0DTD1_1).…”
mentioning
confidence: 99%
“…SARS-CoV-2, is the novel beta coronavirus of the Coronaviridae family whose genome is composed of a single stranded RNA molecule [ 173 ]. It has been shown that hemin, hemoglobin and protoporphyrin IX bind to SARS-CoV-2 proteins, blocking its adsorption and replication independently from HO-1 induction [ 174 ]. However, the current literature regarding HO-1′s antiviral effect against SARS-CoV-2 remains unclear.…”
Section: Unveiling How Ho-1 Promotes Viral Clearancementioning
confidence: 99%
“…[235][236][237] A long series of publications have regarded the possible SARS-CoV-2 interaction with erythrocytes and the consequent hemoglobin dysfunction, with release of free circulating hemoglobin/heme. 21,22,126,130,238,239 More importantly, a few researchers highlighted clear erythrocyte membrane alterations in COVID-19 patients. 4 These and previous data seem to demonstrate furthermore the CD147/SA-based interaction of SARS-CoV-2 with RBC which, at least partially, explains the consequent hemoglobin/iron cycle alteration.…”
Section: A) Sialic Acidmentioning
confidence: 99%
“…Nearly 75% of human iron is contained in hemoglobin; in view of the iron deranged metabolism in COVID-19, a number of articles have investigated a possible hemoglobin denaturation in these patients 1,3,22,61,124,[126][127][128] Though no sound evidence of a direct hemoglobin viral attack has been documented so far, free circulating heme has been described in a few papers 130,238,239 ; moreover, some recruitment of hemoglobin and its metabolites (hemin and protoporphyrin IX) by a few SARS-CoV-2 proteins was documented in a computational biology study. 239 An analogue scientific debate is underway about the alteration of the dissociation curves of hemoglobin in these patients, regardless of whether hypoxia may not be regarded as solely generated by pneumolysis/lung disease. [143][144][145]305 h) Potential environmental, genetic and microbiome susceptibility factors Beside AB0 group and sickle cell conformation, several other factors may predispose to SARS-CoV-2 pathogenicity.…”
Section: G) Hemoglobin Hemementioning
confidence: 99%